Innovative Approaches to Increasing the Competitiveness of Production in Mechanical Engineering. Issue 6 (2nd June 2016) - Katerinich, D.S.
Abstract : Using the example of the mechanical engineering sector of the Republic of Belarus, the article analyzes approaches to maintaining product competitiveness, describes the tools for shaping the sector's technical level, determines strategic directions for implementing an innovational policy, and examines a path toward cooperation with the country's leading institutes of higher education in order to implement innovative activity in the sector's businesses and to increase the level of training for the engineering corps.